A study on correlation of waist indices with body mass index among school children in North Kerala - K., Divya Krishnan; K. P., Shyna; K. V., Urmila; K. V., Anand (International Journal of Contemporary Pediatrics, 2020)
Background: Childhood obesity is a serious problem worldwide. Body mass index (BMI) has been the widely used tool to detect obesity. Central adiposity detected by waist indices is a better predictor of obesity related complications like metabolic syndrome. Objective of this study was to analyze the correlation of waist indices with BMI as indicators of overweight (OW)/obesity in school going children. Methods: This study was done in 880 adolescents from two schools in Kerala. Anthropometric measurements including waist circumference (WC) were taken according to guidelines and BMI, waist hip ratio (WHR), waist height ratio (WHtR) calculated. We categorized children as normal, OW/obese according to BMI charts by centers for disease control and prevention (CDC). A cutoff 70th centile in WC charts by Khadilkar et al, WHR of more than 0.85 in girls and 0.9 in boys, WHtR >0.5 were taken as central obesity. Results: The prevalence of overweight/obesity (BMI >85th centile) was estimated to be 26.3%. Prevalence of central obesity was 12.3% when measured by WC, 22.8% measured by WHR, 14.8% measured by WHtR. All three waist indices showed statistically significant correlation with OW/obesity and BMI (p<0.001). Multivariate regression showed association of OW/obesity with urban school, acanthosis nigricans, hypertension, WHtR (p<0.001) and with WC (p=0.004). Conclusions: The prevalence of overweight and obesity is alarmingly high in adolescent children. Waist height ratio was best correlated with Body mass index and overweight/obesity, followed by Waist circumference. We recommend waist height ratio as a screening tool to predict obesity in school going children.